Relación pedagógica e interacción comunicativa (2012)
ABSTRACT: This paper aims at showing a way of providing teaching, taking in account constant tensions and questions that, going beyond a particular case drawn from experience in the field, allows the sharing of everyday situations in the classroom, which may turn itself into a privileged experience of communicative interaction. Basic concepts of analytical work with groups are compared, especially the transference, and some categories of semio-linguistic discourse analysis, particularly the principles of otherness, relevance, control and influence posed by Patrick Charadeau (1995), in order to build general reflections on educational links and what it means to teach and learn.